Aging Might Increase the Incidence of Infection from Permanent Pacemaker Implantation. (28th November 2013) - Lin, Yun; Li, Zhi Zhong; Zhang, Jingmei; Zhang, Jinrong; Fan, Qian; Du, Jie
Abstract : Aim . The elderly are the major population receiving the implantation of a permanent pacemaker (PPM). Infection is a devastating complication. The present study is to verify the relationship between age and PPM implantation infection. Methods . All patients (162 adult and 292 elder patients) received the implantation of PPM. Subcutaneous tissue samples solution was collected in three time points, the first sample was got at skin incision, and the second sample was got when the PPM had been implanted. And the third sample was got after 0.9% NaCl quick rinse. And the tissue solutions were cultured. If culture results are positive, it is considered as evidence of the presence of bacteria in pocket in operation of PPM implantation. Results . The data demonstrated that compared with that in the adult patients, subcutaneous bacterial survival rate was higher significantly in the elderly. Staphylococcus epidermidis is the major bacterial strain. The rinse decreased subcutaneous bacterial survival rates in the adult group. Conclusion . With the age increasing, PPM implantation might be easier to result in infection. Simple rinse can prevent implantation infection significantly. However, age alleviated the protective effects of rinse. Therefore, we should pay more attention to post implantation infection in the elderly.